The three facets of the SARS-CoV-2 pandemic during the first two waves in the northern, central, and southern Italy - Silvio Buscemi; Chiara Davoli; Enrico Maria Trecarichi; Helen Linda Morrone; Bruno Tassone; Carola Buscemi; Cristiana Randazzo; Anna Maria Barile; Piero Colombrita; Maurizio Soresi; Lydia Giannitrapani; Antonio Cascio; et al. (Elsevier, 2023)
Background: There is a scarcity of information in literature regarding the clinical differences and comorbidities of patients affected by Coronavirus disease 2019 (COVID-19), which could clarify the different prevalence of the outcomes (composite and only death) between several Italian regions. Objective: This study aimed to assess the heterogeneity of clinical features of patients with COVID-19 upon hospital admission and disease outcomes in the northern, central, and southern Italian regions. Methods: An observational cohort multicenter retrospective study including 1210 patients who were admitted for COVID-19 in Infectious diseases, Pulmonology, Endocrinology, Geriatrics and Internal Medicine Units in Italian cities stratified between north (263 patients); center (320 patients); and south (627 patients), during the first and second pandemic waves of SARS-CoV-2 (from February 1, 2020 to January 31, 2021). The data, obtained from clinical charts and collected in a single database, comprehended demographic characteristics, comorbidities, hospital and home pharmacological therapies, oxygen therapy, laboratory values, discharge, death and Intensive care Unit (ICU) transfer. Death or ICU transfer were defined as composite outcomes. Results: Male patients were more frequent in the northern Italian region than in the central and southern regions. Diabetes mellitus, arterial hypertension, chronic pulmonary and chronic kidney diseases were the comorbidities more frequent in the southern region; cancer, heart failure, stroke and atrial fibrillation were more frequent in the central region. The prevalence of the composite outcome was recorded more frequently in the southern region. Multivariable analysis showed a direct association between the combined event and age, ischemic cardiac disease, and chronic kidney disease, in addition to the geographical area. Conclusions: Statistically significant heterogeneity was observed in patients with COVID-19 characteristics at admission and outcomes from northern to southern Italy. The higher frequency of ICU transfer and death in the southern region may depend on the wider hospital admission of frail patients for the availability of more beds since the burden of COVID-19 on the healthcare system was less intense in southern region. In any case, predictive analysis of clinical outcomes should consider that the geographical differences that may reflect clinical differences in patient characteristics, are also related to access to health-care facilities and care modalities. Overall, the present results caution against generalizability of prognostic scores in COVID-19 patients derived from hospital cohorts in different settings.